Insights into mildly dilated cardiomyopathy: temporal evolution and long‐term prognosis. (4th November 2016) - Gigli, Marta; Stolfo, Davide; Merlo, Marco; Barbati, Giulia; Ramani, Federica; Brun, Francesca; Pinamonti, Bruno; Sinagra, Gianfranco
Abstract: Aims: Mildly dilated cardiomyopathy (MDCM) has been proposed as a subtype of dilated cardiomyopathy (DCM) characterized by systolic dysfunction in the absence of significant LV dilatation. Few data on the characteristics and outcomes of MDCM patients are available. We sought to assess the main features and the long‐term natural history of MDCM. Methods and results: From 1988 to 2010 we analysed all DCM patients consecutively evaluated at our Institution. MDCM was defined as LVEF <45% and LV end‐diastolic volume index (LVEDVI) ≤70 mL/m 2 in women and ≤89 mL/m 2 in men. Among a total population of 638 patients, 226 (35%) fulfilled the criteria for MDCM. Compared with the other patients, they presented features of a less advanced disease and an overall long‐term lower rate of all‐cause mortality/heart transplantation (D/HTx; total events = 209; 144 deaths, 65 HTx): D/HTx at 10 years 15% in MDCM vs. 30% in DCM ( P < 0.001). However, throughout the follow‐up, 55 MDCM patients (24%) evolved to DCM by increasing LVEDVI, consistently worsening their long‐term prognosis. Among persistent MDCM patients, a restrictive filling pattern [hazard ratio (HR) 5.30; 95% confidence interval (CI) 2.34–12.01, P < 0.001] and non‐sustained ventricular tachycardia (HR 2.21; 95% CI 1.003–5.11, P = 0.047), but not LVEF, were independently associated with D/HTx at multivariate analysis [time‐dependent receiver operating characteristic (ROC) curve: area under the curve (AUC) 0.80, 95% CI 0.65–0.94, P = 0.003]. Conclusions: MDCM identifies a consistent subgroup of DCMs diagnosed in an earlier stage and presenting an apparent better evolution. However, some MDCMs evolve into DCM despite medical therapy, whereas persistent MDCMs with non‐sustained ventricular arrhythmias and restrictive filling pattern are characterized by a very poor outcome.